2022
DOI: 10.1002/adfm.202204991
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Porous N‐Doped Carbon with Sulfonic Acid toward High‐ICE/Capacity Anode Material for Potassium‐Ion Batteries

Abstract: Among anode materials for potassium‐ion batteries (PIBs), carbon‐based materials attract extensive attention due to their abundant material resources, low cost, high surface capacity, and excellent electrical conductivity. However, carbon‐based materials always display a low initial coulombic efficiency (ICE), which greatly hinders the full utilization of the battery capacity and energy density. Moreover, the slow dynamic process and the large volume expansion during intercalation result in poor cyclic stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 63 publications
1
30
1
Order By: Relevance
“…6 j). Paradoxically, the adsorption energy was even lower than that of N doping after N/S doping, which was different from the results obtained in most recent reports [ 41 , 52 ], indicating that S doping did not contribute to the adsorption of K + . S dopants (C-S-C) created specific defect sites, which was also a prerequisite for the formation of edge defects in amorphous carbons.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…6 j). Paradoxically, the adsorption energy was even lower than that of N doping after N/S doping, which was different from the results obtained in most recent reports [ 41 , 52 ], indicating that S doping did not contribute to the adsorption of K + . S dopants (C-S-C) created specific defect sites, which was also a prerequisite for the formation of edge defects in amorphous carbons.…”
Section: Resultscontrasting
confidence: 99%
“…The infrared absorption peaks near 900 and 1370 cm ‒1 corresponded to the triazine ring. Meanwhile, the infrared absorption peaks of C-S (~ 490 and 704 cm ‒1 ) [ 41 ], N–H (~ 760 cm ‒1 ), C-N (~ 1200 cm ‒1 ), and C = N (~ 1650 cm ‒1 ) bonds were clearly observed. The enhanced absorption peaks near 1615, 1495, and 1410 cm –1 (phenylpropane monomer) [ 42 ] proved that LS had been successfully assembled in the as-synthesized supermolecule.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between the peak current ( i ) and the scan rate (ν) can be obtained by the following formula i = a v b where a and b are variables . Usually, the behavior of diffusion or capacitance control can be determined with a b value of 0.5 or 1, respectively . The cathodic b values of 0.779, 0.824, and 0.892 for CA, CAB, and CABP electrodes, respectively (Figure f), indicate mixed controlled behavior, while the b values for the three materials are increasing, with CABP having a b value closest to 1, due to the greatest abundance of pores and heteroatoms in the CABP .…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, considering resource abundance (1.5 wt%), cost‐effectiveness (e.g., K 2 CO 3 ), and similar working mechanism to LIBs, [ 3 , 5 , 6 ] potassium‐ions batteries (PIBs) have attracted enormous attention in recent years, and are theoretically demonstrated to be able to provide high voltage platform and high energy density, resulting from a low redox potential of K/K + versus standard hydrogen electrode (−2.93 V, that is closed to −3.04 V of Li/Li + ). [ 1 , 7 , 8 ] Accordingly, a large number of related studies have been reported, especially for anode materials, which significantly promote the development of PIBs.…”
Section: Introductionmentioning
confidence: 99%
“…Commercialized lithium-ion batteries (LIBs) are the most commonly used energy storage devices in the past two decades and DOI: 10.1002/advs.202205234 are currently applied in electric vehicles, [1,2] due to their high energy density and long cycle life, etc. However, based on the long-term sustainable perspective, limited lithium resources (0.0017 wt% in the earth crust) and ever-increasing cost will inevitably hamper its further development, [3,4] which prompts researchers to explore alternatives to LIBs urgently.…”
Section: Introductionmentioning
confidence: 99%